2020
DOI: 10.7759/cureus.11207
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Hearing Loss in Neonates Admitted to the Neonatal Intensive Care Unit: A Hospital Study

Abstract: Introduction: Hearing loss is one of the most common congenital disabilities in neonates. The aims of this study were to investigate the prevalence of hearing loss and identify the most significant risk factor in neonates hospitalized at the Neonatal Intensive Care Unit (NICU). Methods: This cross-sectional study involved 530 neonates admitted to NICU Abuzar Hospital with risk factors for hearing loss based on Joint Committee of Infant Hearing (JCIH). The hearing screening tests include transient evoked otoaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 18 publications
1
4
0
1
Order By: Relevance
“…In the present study, there was no statistical significance regarding birth weight as well as prematurity with hearing loss. This is in agreement with (Hardani et al, 2020). However, in contrast to this finding, a study conducted by (Regina et al, 2017) reported that 31.5% and 28.9% of newborns suffering from hearing impairment were born prematurely (gestational age ≤ 36 weeks) and were of low birth weight (˂ 1500 gm) respectively.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the present study, there was no statistical significance regarding birth weight as well as prematurity with hearing loss. This is in agreement with (Hardani et al, 2020). However, in contrast to this finding, a study conducted by (Regina et al, 2017) reported that 31.5% and 28.9% of newborns suffering from hearing impairment were born prematurely (gestational age ≤ 36 weeks) and were of low birth weight (˂ 1500 gm) respectively.…”
Section: Discussionsupporting
confidence: 80%
“…Also, (Wroblewska-Seniuk et al, 2017) who performed a study on preterm neonates found that the most frequent risk factor in preterm neonates ˂ 33 weeks was exposure to ototoxic medications (63%) followed by low birth weight ˂ 2500 g (53.3%) and treatment in the NICU (43.9%). The use of ototoxic medications was also the most frequent risk factor in neonates ˃ 33 weeks of gestation (1.72%) in another study conducted by (Hardani et al, 2020) in which 530 infants with different risk factors were screened. It found that ototoxic drugs and hyperbilirubinemia requiring exchange transfusion were the commonest risk factors followed by asphyxia, low birth weight weight, Apgar score ˂ 5.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that hearing loss is more prevalent in newborns admitted to the Neonatal Intensive Care Unit (NICU) [ 16 ]. A systematic review and meta-analysis by Butcher et al showed that prevalence of permanent childhood hearing loss was 6.9 times higher among those admitted to NICU [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study on 530 neonates admitted to NICU Abuzar Hospital in Ahvaz, Iran, 5.09% were diagnosed with different types of hearing loss. Findings of the study revealed that hearing loss is associated with antibiotic therapy [ 16 ]. Recchia et al also suggested that use of ototoxic drugs is one of the causes of hearing loss in infants hospitalized in the NICU [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini dapat dijelaskan dengan perubahan ambang dengar yang bergantung pada maturitas auditorik pada jalur perifer maupun neural, umumnya terjadi gangguan fungsi sel rambut luar koklea disebabkan oleh belum maturnya organ koklea baik anatomi dan fungsinya sehingga sebagian ditemukan kejadian gangguan pendengaran sementara pada anak dengan prematuritas. 3,14 Penelitian ini menunjukkan tidak terdapat hubungan yang signifikan antara BBLR dengan derajat gangguan pendengaran (r = 1,815; CI 95% = 0,684 -4,820; p = 0,158). Hasil ini sesuai dengan penelitian sebelumnya pada 600 neonatus di Zanzibar melaporkan tidak ada hubungan yang signifikan antara BBLR dengan derajat gangguan pendengaran (p = 0.804), hasil penelitian ini, tidak sesuai dengan penelitian Nisotakis dan Chalkiadakis yang melaporkan bahwa BBLR berhubungan dengan kejadian gangguan pendengaran (p = 0,05).…”
Section: Diskusiunclassified